Evaluating Community Health Care Providers Knowledge and Self-Confidence in the Identification, Diagnosis and Treatment of Adolescent Depression in Tanzania - Stan Kutcher; Yifeng Wei; Heather Gilberds; Adena Brown; Omary Ubuguyu; Tasiana Njau; Norman Sabuni; Ayoub Magimba; Kevin Perkins (Archives of Depression and Anxiety - Peertechz Publications, 2016)
Background: Depression, which frequently onsets in young people, is projected to become the largest single burden of disease globally in the next decade. Its impact may be disproportionally felt in low-income countries, such as Tanzania, where availability of appropriate care in the community is poor. As part of the development of a health provider work force that can properly address this issue, assessment of current mental health literacy, focusing on knowledge about and self-confidence in the identification, diagnosis and treatment of Depression in young people by community health care providers is needed. This study addresses that need. Methods:  As part of the Integrated Approach to Addressing Depression amongst Youth in Malawi and Tanzania project funded by Grand Challenges Canada and supported by the Ministry of Health and Social Welfare, we evaluated the knowledge and self-confidence of 109 community based health care providers (HCP) in the Arusha and Meru Districts of Tanzania. Results:  Results demonstrate that baseline knowledge about adolescent Depression among HCP's was poor with a group average score of 55%. However, HCP's demonstrated high rates of self-confidence regarding their ability to identify, diagnose and treat adolescent Depression. Conclusions: To our knowledge this is the first study investigating these parameters in a cohort of community HCP's in Tanzania (and perhaps all of Sub-Saharan Africa) these findings provide valuable  information regarding HCP's  knowledge about adolescent  Depression. The disconnect between high self-confidence and low level of knowledge suggests that quantitative assessment of baseline  competencies in mental health care is necessary  when  determining  future  mental  health care training needs in this population.This study further indicates the importance of providing training of HCP on adolescent Depression to address the gap between knowledge and self-confidence.